Enhancing the Use of Products with Recycled Contents in the Australian Construction Industry - Shooshtarian, Salman; Maqsood, Tayyab; Zaman, Atiq; Caldera, Savindi; Ryley, Tim; Wong, Peter SP (Nova Science Publishers, Inc., 2024)
This book presents an extensive review of various national and international literature, an analysis of relevant policies and guidelines, and an evaluation of key stakeholders’ sentiments. It provides valuable insights into five key areas: (1) analysis of national and jurisdictional policy frameworks that affect the creation and stimulation of end-markets for waste materials; (2) assessment of the operation of existing end-markets for five strategic construction materials; (3) exploration of the application of sustainable procurement policies and practices at state, national and international levels; (4) evaluation of impacts of COVID-19 on construction and demolition waste industry; and (5) identification of key factors affecting construction and demolition waste end-market creation and stimulation, and building a model for waste market development.